Mixed adenoneuroendocrine tumour with squamous differentiation: a case report - Thomas, Irene; Surendran, Divya; Augustine, Joy (Journal of Pathology of Nepal, 2021)
Mixed adenoneuroendocrine carcinoma is a rare neoplasm with both epithelial and neuroendocrine components. To date, only a few cases of this neoplasm have been reported in the literature among which gastric mixed adenoneuroendocrine carcinoma is very rare. We are reporting a case of gastric mixed adenoneuroendocrine carcinoma with squamous cell differentiation. Histopathological features, biological behaviour and the treatment of this rare tumour type have been discussed briefly.